2022
DOI: 10.1002/jmd2.12270
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of sulfatides in the amniotic fluid supernatant: A useful tool in the prenatal diagnosis of metachromatic leukodystrophy

Abstract: Metachromatic leukodystrophy (MLD) is an autosomal recessive lysosomal disorder caused by deficiency of arylsulfatase A (ARSA), leading to an accumulation of sulfatides. Sulfatides have been quantified in urine, dried blood spots (DBS), and tissues of patients with MLD. Newborn screening (NBS) for MLD has already been proposed based on a two-tier approach with the quantification of sulfatides in DBS followed by the quantification of ARSA by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Prenatal sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A study by Kubaski et al showed the importance of newborn screening for diagnosing MLD. They have proposed double amniotic fluid screening for sulfatides [ 8 ]. This was not similar to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kubaski et al showed the importance of newborn screening for diagnosing MLD. They have proposed double amniotic fluid screening for sulfatides [ 8 ]. This was not similar to the present study.…”
Section: Discussionmentioning
confidence: 99%